Improving luminous flux and color homogeneity of dual-layer phosphor sctructure - Tran Thanh Trang; Phan Xuan Le; Nguyen Doan Quoc Anh (Universitas Ahmad Dahlan, 2019)
In order to clarify the main purpose of the study, we put a green phosphor layer SrBaSiO4:Eu2+ on the yellow phosphorus layer YAG:Ce3+ through using only one WLEDs structure in different color temperatures like 5600 K, 6600 K, 7700K. Then, we find the suitable SrBaSiO4:Eu2+ concentration in order that the luminous flux could get the highest value. The results show that SrBaSiO4:Eu2+ brings great benefits to increase not only optical gain but also color uniformity. Specifically, the greater the SrBaSiO4:Eu2+ concentration, the greater the output of WLEDs because of the development of green light component in WLEDs. However, only if the SrBaSiO4:Eu2+ concentration exceeds the level, a slight decrease in color rendering index (CRI) can occur, which based on Monte Carlo simulation. In addition, the results of this paper have contributed significantly to the creation of higher-powered WLEDs.